Breaking Language Barriers with a LEAP: Learning Strategies for Polyglot LLMs - Balloli, Vaibhav; Ranjit, Mercy; Nambi, Akshay; Ganu, Tanuja; Ahuja, Kabir; Sitaram, Sunayana; Bali, Kalika (2023)
Large language models (LLMs) are at the forefront of transforming numerous domains globally. However, their inclusivity and effectiveness remain limited for non-Latin scripts and low-resource languages. This paper tackles the imperative challenge of enhancing the multilingual performance of LLMs, specifically focusing on Generative models. Through systematic investigation and evaluation of diverse languages using popular question-answering (QA) datasets, we present novel techniques that unlock the true potential of LLMs in a polyglot landscape. Our approach encompasses three key strategies that yield remarkable improvements in multilingual proficiency. First, by meticulously optimizing prompts tailored for polyglot LLMs, we unlock their latent capabilities, resulting in substantial performance boosts across languages. Second, we introduce a new hybrid approach that synergizes GPT generation with multilingual embeddings and achieves significant multilingual performance improvement on critical tasks like QA and retrieval. Finally, to further propel the performance of polyglot LLMs, we introduce a novel learning algorithm that dynamically selects the optimal prompt strategy, LLM model, and embeddings per query. This dynamic adaptation maximizes the efficacy of LLMs across languages, outperforming best static and random strategies. Our results show substantial advancements in multilingual understanding and generation across a diverse range of languages.